Investigation of Fault Current Limiting Methods in Power Systems - Akay, Nihat; Arikan, Oktay; Karacasu, Ozgur (IEEE, 2016)
The growing demand for electrcity consumption results in increasing complexity and continous expansion of power systems. By the connection of new power plants, lines and loads to grid, the level of transfered energy and fault currents increases accordingly. As a result of this phenomenon, equipment breakdowns and even system blackouts may occur. Thus, limiting of fault currents becomes a critical problem to be solved by system operators. Within this perspective, several fault current limiter methods are studied and an example on fault current limiting application on a sample part of Turkish Transmission System is presented. The results indicate that fault current limiters come out as an effective solution for transformer substations operating close to their short circuit withstand limits.
Keywords: Engineering